(untitled) (Conferencea, 2022)
The first theoretical ideas about translation originated in ancient Rome. The first studies devoted to the theory of translation began to appear in the twenties of the last century. Studies defining and advocating translation theory as a science began to be published by the fifties of the century. The monograph "Language and translation" made a great contribution to the further development of the science of translation theory in Uzbekistan. According to Linguist Katharina Rice, the main situation in the practice of translation must depend on the diversity of the text.